TAYANGAN KEKERASAN DI TELEVISI DAN TERPAANNYA PADA KHALAYAK MASYARAKAT - Mahmudah, Dede (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
Since its presence, television has contributed hugely to the development of mass media. However, it seems no day without violence in television programs in Indonesia,. Based on various studies that have been done, theories constantly developed, as well as various hypotheses proposed by many experts, it is clear that television programs presenting violences can significantly increase the emergence of violences in real life. Television which is expected to be an effective media to obtain various information and to gain knowledge for the audience, in fact make people accustomed to seeing violence exposure. People even regard the acts of violence as common thing and begin to emulate. Consequently, caring for victims has faded away, or even disappeared since violence is considered as normal thing to do. Therefore, in-depth research related to the impact of violence on television is still needed, in order to obtain patterns and factors that can trigger violence depicted in television shows, as well as finds the best ways to pr event and overcome violence.